Near-Infrared Spectroscopy Enhances Intravascular Ultrasound Assessment of Vulnerable Coronary Plaque: A Combined Pathological and In Vivo Study. Issue 11 (November 2015) - Puri, Rishi; Madder, Ryan D.; Madden, Sean P.; Sum, Stephen T.; Wolski, Kathy; Muller, James E.; Andrews, Jordan; King, Karilane L.; Kataoka, Yu; Uno, Kiyoko; Kapadia, Samir R.; Tuzcu, E. Murat; et al.
Abstract : Objectives—: Pathological studies demonstrate the dual significance of plaque burden (PB) and lipid composition for mediating coronary plaque vulnerability. We evaluated relationships between intravascular ultrasound (IVUS)–derived PB and arterial remodeling with near-infrared spectroscopy (NIRS)–derived lipid content in ex vivo and in vivo human coronary arteries. Approach and Results—: Ex vivo coronary NIRS and IVUS imaging was performed through blood in 116 coronary arteries of 51 autopsied hearts, followed by 2-mm block sectioning (n=2070) and histological grading according to modified American Heart Association criteria. Lesions were defined as the most heavily diseased 2-mm block per imaged artery on IVUS. IVUS-derived PB and NIRS-derived lipid core burden index (LCBI) of each block and lesion were analyzed. Block-level analysis demonstrated significant trends of increasing PB and LCBI across more complex atheroma ( P trend <0.001 for both LCBI and PB). Lesion-based analyses demonstrated the highest LCBI and remodeling index within coronary fibroatheroma ( P trend <0.001 and 0.02 versus all plaque groups, respectively). Prediction models demonstrated similar abilities of PB, LCBI, and remodeling index for discriminating fibroatheroma ( c indices: 0.675, 0.712, and 0.672, respectively). A combined PB+LCBI analysis significantly improved fibroatheroma detection accuracy ( c index 0.77, P =0.028 versus PB; net-reclassification index 43%, P =0.003), whereas further adding remodeling index did not ( c index 0.80, P =0.27 versus PB+LCBI). In vivo comparisons of 43 age- and sex-matched patients (to the autopsy cohort) undergoing combined NIRS-IVUS coronary imaging yielded similar associations to those demonstrated ex vivo. Conclusions—: Adding NIRS to conventional IVUS-derived PB imaging significantly improves the ability to detect more active, potentially vulnerable coronary atheroma. Abstract : Supplemental Digital Content is available in the text.